Empowering community through entrepreneurship training and Islamic micro-financing: sharing the experience of IIUM-CIMB Islamic smart partnership (i-Taajir) - Md Saad, Norma; Mohammed, Mustafa Omar; Haneef, Mohamed Aslam (IGI Global, 2020)
Community economic development is a relatively new strategy employed to increase employment, income, and entrepreneurship activities in small town and communities. The Centre for Islamic Economics, International Islamic University Malaysia (IIUM) has initiated a smart partnership with CIMB Islamic Bank to offer entrepreneurship training and Islamic microfinance facility to the poor in Malaysia. This project adopts several modes of Islamic microfinance financing instruments which include equity-based and debt-based financing. The program aims to educate the communities surrounding the IIUM campus with entrepreneurship knowledge and skill in addition to giving Shariah-compliant micro-financing facility for them to implement their business ideas. CIMB Islamic, which is the main partner for this project, provides funds for Islamic microfinance facilities and IIUM contributes expertise in providing entrepreneurship trainings to the communities located near IIUM campus. It is hoped that this smart partnership would empower the surrounding communities and create more successful entrepreneurs.